Attitudes of Al Jabel Al Akhder Region Residents Towards Tourism - البدري, عبدالقادر; العوامي, احمد (Dirasat in Economics and Business, 2007)
The aim of this study is to measure and evaluate the attitudes of the Libyan residents of Al Jabel Al Akhder towards tourism and to indicate their knowledge of the positive and negative aspects of tourism and their awareness of the importance of availability of the constituents of tourism in their areas as well as to know if there is relation between their attitudes and their personal characteristics. The study concluded that the local residents in Al Jabel Al Akhder Region have negative attitudes toward tourism The study also revealed that there lack of relation between the personal characteristics of the local residents and their attitude towards tourism. The study has suggested a number of recommendations which contribute in the development and support of tourism sector in Al Jabel Al Akhder Region.